Optimization of lavender (Lavandula angustifolia) callus culture - Keykha, Fatemeh; Khadem, Azade; Bagheri, Abdolreza; Sharifi, Ahmad; Ameri, Maryam (Plant Tissue Culture and Biotechnology, 2015)
Abstract not available Plant Tissue Cult. & Biotech. 24(2): 279-285, 2014 (December)